2021
DOI: 10.1049/mna2.12082
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of antibacterial silver nanoparticles using essential oils of crown imperial leaves, bulbs and petals

Abstract: In this research, the essential oils obtained from leaves, bulbs and petals of crown imperial plant are used as reducing agents to fabricate silver nanoparticles. The aromatic hydrocarbons, alkenes, ketenes and alkaloids are among the compounds identified in the essential oils as detected by gas chromatography mass spectrometry. The characteristics of silver nanoparticles are investigated by field emission scanning electron microscopy, transmission electron microscopy and XRD. The chemical groups and surface r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The TG-containing scaffolds have a more hydrophilic nature as understood from lower contact angles than the PVA/β-S sample. It is found that the PVA/β-S/TG hybrid fibers have a contact angle between PVA and PVA/β-S. Because of their higher hydrophilicity and water-solubility, the TG-containing samples have a lower contact angle than PVA/β-S scaffold due to the TG water-soluble fraction [5,20]. It is noted that the PVA/β-S/TG 0.5% sample is regarded as more hydrophilic than PVA/β-S/TG 1%, representing the optimally fabricated sample in view of hydrophilicity.…”
Section: Contact Anglementioning
confidence: 99%
See 1 more Smart Citation
“…The TG-containing scaffolds have a more hydrophilic nature as understood from lower contact angles than the PVA/β-S sample. It is found that the PVA/β-S/TG hybrid fibers have a contact angle between PVA and PVA/β-S. Because of their higher hydrophilicity and water-solubility, the TG-containing samples have a lower contact angle than PVA/β-S scaffold due to the TG water-soluble fraction [5,20]. It is noted that the PVA/β-S/TG 0.5% sample is regarded as more hydrophilic than PVA/β-S/TG 1%, representing the optimally fabricated sample in view of hydrophilicity.…”
Section: Contact Anglementioning
confidence: 99%
“…This method allows one to better connect the cathodic side of a polarized electrode to a reservoir [17]. The ability to use electrospinning on natural and synthetic polymers offers a wide range of biomedical applications [17,18], such as drug delivery, tissue engineering, and wound dressing [3,5,19,20]. Electrospinning is a one-of-a-kind technique that allows sufficiently nanoscale biomaterials to be designed and adjusted for enhanced differentiation, proliferation, and cell migration at the injured site, as well as tissue regeneration post-treatment [21].…”
Section: Introductionmentioning
confidence: 99%
“…In the process of synthesis of nanoparticles, the plant derived essentials oils which are concentrated hydrophobic liquids containing volatile aroma compounds act as both reducing and stabilizing agents. In literature, various plant essential oils for the fabrication of metal nanoparticles including silver [15][16][17][18][19][20][21], titanium dioxide [22], iron [23], gold [24], magnesium [25], copper [26], etc. are reported.…”
Section: Introductionmentioning
confidence: 99%
“…Still chemical reductants are expensive and can negatively affect the environment. Therefore, it is unsuitable for some research and applications ( Zakeri et al., 2021 ; Pang et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%